Effects of Music Training on Social, Behavioral, and Academic Skills of Children with Cochlear Implants from the School Teacher's Perspective - Martins-Said, Paula; Alvarenga, Kátia de Freitas; Abramides, Dagma Venturini Marques (International Archives of Otorhinolaryngology, 2025)
Music has been recognized as a therapeutic tool in auditory rehabilitation, promoting essential social and behavioral development in children with cochlear implants (CIs), as identified by the World Health Organization (WHO). Additionally, there is a lack of studies on the development of these skills in this context.To investigate the effect of music training on the development of social, behavioral, and academic skills in children with CIs from the schoolteacher's perspective.The present is an experimental study involving 10 children with CIs, aged between 6 and 10 years, who composed the experimental group. They had a semester of music training and were assessed through the Social Skills Rating System (SSRS) questionnaire at 4 different moments: 2 months before the beginning of the music training, at the beginning of the music training (first week of class), during the music training (3 months after the beginning), and at the end of the music training (6 months after the beginning). To compare the multiple SSRS assessments, we used the repeated measures analysis of variance (ANOVA) test and the Tukey test (p ≤ 0.05).The results showed a statistically significant improvement in social skills in terms of assertiveness, social resourcefulness, self-control, affectivity, cooperation, externalizing behavior problems, and academic competence.From the schoolteacher's perspective CI-using children who had music training experienced an improvement in their social and academic skills and behavioral problems.
Keywords: music; deafness; cochlear implantation; social skills